Optimization Of Productive Zakat As An Effort To Empower The Economy Of The People - Mutmainah, Siti (EMPOWERING HUMANITY, 2023)
The problem of poverty occurs due to social inequality between the capable population and the underprivileged population, besides that the lack of awareness between residents to help each other is also one of the causes of poverty in Indonesia. In overcoming the problem of poverty, productive zakat is considered capable of empowering the economy of Muslims. The research method used in this study is a literature study study using data from journals, other reliable sources.The results of this study show that productive zakat distributionin the form of business capital is one of the efforts to empower the people's economy, so that mustahiks who initially only depended on zakat funds can make their own money from capital obtained from productive zakat. One of the purposes of productive zakat distribution is to change the position of mustahik to muzakki. Therefore, in the future, it is hoped that the distribution of productive zakat will continue to be carried out and improved so that it can be distributed to more mustahiks who are entitled and have the potential so that the problem of poverty that has always haunted can be eliminated immediately.